2016
DOI: 10.1021/acs.jpcc.5b11616
|View full text |Cite
|
Sign up to set email alerts
|

Hindered Translator and Hindered Rotor Models for Adsorbates: Partition Functions and Entropies

Abstract: With the recent explosion in computational catalysis and related microkinetic modeling, the need for a fast yet accurate way to predict equilibrium and rate constants for surface reactions has become more important. Here we present a fast and accurate new method to estimate the partition functions and entropies of adsorbates based on quantum mechanical estimates of the potential energy surface. As with previous approaches, it uses the harmonic oscillator (HO) approximation for most of the modes of motion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
198
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(203 citation statements)
references
References 41 publications
(123 reference statements)
4
198
0
1
Order By: Relevance
“…The next step is to estimate values of binding energies for adsorption of all species on the surface, for example using experimental results from the literature, results from DFT calculations, or scaling relations (20)(21)(22)(23)(24). In addition, it is necessary to estimate values for the entropies of the adsorbed species, for example using results from experimental studies (25), correlations in the literature (26), results from DFT calculations of vibrational frequencies (27)(28)(29)(30)(31)(32)(33)(34), combined with hindered translator and hindered rotor models for the three modes associated with motion parallel to the surface (35,36), or by assuming models for the extent of mobility on the surface. It is now possible to estimate values for lumped equilibrium constants, K ads,i , to form the adsorbed species from the reactants and/or products, followed by calculation of θ p .…”
Section: Analytical Strategy For Analysis Of Reaction Schemesmentioning
confidence: 99%
“…The next step is to estimate values of binding energies for adsorption of all species on the surface, for example using experimental results from the literature, results from DFT calculations, or scaling relations (20)(21)(22)(23)(24). In addition, it is necessary to estimate values for the entropies of the adsorbed species, for example using results from experimental studies (25), correlations in the literature (26), results from DFT calculations of vibrational frequencies (27)(28)(29)(30)(31)(32)(33)(34), combined with hindered translator and hindered rotor models for the three modes associated with motion parallel to the surface (35,36), or by assuming models for the extent of mobility on the surface. It is now possible to estimate values for lumped equilibrium constants, K ads,i , to form the adsorbed species from the reactants and/or products, followed by calculation of θ p .…”
Section: Analytical Strategy For Analysis Of Reaction Schemesmentioning
confidence: 99%
“…We note that dispersion corrections can influence both the vibrational frequencies and the adsorption entropy to a significant extent. For instance, Sprowl et al reported differences of as high as 3.0R in the calculated entropy using their hindered translator/rotor approach, depending on whether or not dispersion corrections were included.…”
Section: Discussionmentioning
confidence: 66%
“…The specific contributions of different entropic terms are given in (d) with two standard deviation error. The θ std for ethane was taken from Sprowl et al [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations